New Format of the Final State Examination at Bachelor Graduates in the Field of «Pedagogical Education» - Perevoschikova, Elena N. (2020)
The purpose of this study is to build a model of fund tasks aimed at assessing general professional and universal competencies of bachelor's graduates studying in the field of training «Pedagogical education» at the stage of preparation and conduct of the final state exam. Systemic, action-oriented, competency-based and contextual approaches were used as methodological guidelines in the development of fundraising tasks. The authors defined the notions of "fund task", "key actions" and highlighted the types of fund tasks, justified the need to change the form and content of evaluation tools used in the preparation and conduct of the final state exam.